2003
DOI: 10.1046/j.1365-2109.2003.00851.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative genetic parameter estimates for size and growth rate traits in Pacific white shrimp,Penaeus vannamei(Boone 1931) when reared indoors

Abstract: Heritabilities of size traits and growth rate traits, as well as genetic, phenotypic and environmental correlations were estimated at three ages for a captive population of Pacific white shrimp (Penaeus vannamei) grown indoors. A covariate, mean size or mean growth rate during early growth in individual tanks before tagging and mixing, was introduced in the analyses to reduce the error caused by unique previous growth conditions on variance components. Heritabilities of size traits increased with age, with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 21 publications
3
24
0
Order By: Relevance
“…Estimates of heritability (combined males and females) in F1 at the end of the trial was similar for both lines (0.27 ± 0.11 and 0.34 ± 0.12, LC and LS, respectively), coinciding with results obtained by Pérez-Rostro & Ibarra (2003) in white shrimp Litopenaeus vannamei, where values of 0.20 were obtained at 17 weeks of culture as well and those of Cameron et al (2004) in the red claw crayfish C. quadricarinatus, where a decrease in the value of heritability of 0.38 for the first year to 0.13 after 4 years.…”
Section: Genetic Improvementsupporting
confidence: 73%
See 1 more Smart Citation
“…Estimates of heritability (combined males and females) in F1 at the end of the trial was similar for both lines (0.27 ± 0.11 and 0.34 ± 0.12, LC and LS, respectively), coinciding with results obtained by Pérez-Rostro & Ibarra (2003) in white shrimp Litopenaeus vannamei, where values of 0.20 were obtained at 17 weeks of culture as well and those of Cameron et al (2004) in the red claw crayfish C. quadricarinatus, where a decrease in the value of heritability of 0.38 for the first year to 0.13 after 4 years.…”
Section: Genetic Improvementsupporting
confidence: 73%
“…Estimates of heritability (h 2 ) ± E.S in F1 at the different ages (months), in selection line (LS) and control line (LC) with a value of 1.1 reducing the third month (0.27) have to rise again in the fourth month (0.58). Due to the differential survival and in order to reduce the effect of common environment which is reported in previous studies with crustaceans (Benzie et al, 1997;Hetzel et al, 2000;Pérez-Rostro & Ibarra, 2003), the density of families in the third month were standardized, leaving 11 organisms per family in F1.…”
Section: Genetic Improvementmentioning
confidence: 99%
“…However, due to the effects of genetic linkage, pleiotropy and environmental factors (Toro and Newkirk, 1990;Li et al, 2006;, it has proven difficult to achieve satisfactory results in the selection programs when only taking body weight into account. However, body weight has been found to be highly correlated with many other morphological traits (Pérez-Rostro and Ibarra, 2003). In the present study, abundant variation was found in the 21 morphological traits of L. maculatus.…”
Section: Discussionmentioning
confidence: 63%
“…These methods include correlation analysis, path analysis, and regression analysis. To date, studies of phenotypic and genetic relationships among growth-related traits have been performed in many fish species, including Oncorhynchus mykiss (Kause et al, 2002), Scophthalmus maximus (Wang et al, 2010), Pangasianodon hypophthalmus (Sang et al, 2009), Paralichthys olivaceus (Tian et al, 2011), Penaeus vannamei (Pérez-Rostro and Ibarra, 2003), and Salmo salar (Haffray et al, 2012). For example, nine morphological traits (total length, head length, snout length, body width, head width, interorbital distance, body depth, head depth, and body weight) from juvenile Polyodon spathula were measured, among which total length was the most predominant variable to affect body weight (Yuan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation